2017
DOI: 10.1002/ange.201705644
|View full text |Cite
|
Sign up to set email alerts
|

A Fairly Stable Crystalline Silanone

Abstract: Silanones 2 substituted by bulky amino‐ and phosphonium ylide substituents have been synthesized and isolated in crystalline form. Thanks to the steric protection and the strong electron‐donating ability of the substituents, silanones 2 are persistent and only slowly dimerizes at room temperature (t1/2=0.5 or 5 h). Structural and theoretical analysis of 2 indicate a short Si=O bond (1.533 Å) and an enhanced polarization toward the O atom compared to Me2Si=O owing to the strong π‐electron donation from the phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…Due to the synthetic importance of the carbonyl group, the synthesis of their main‐group analogs containing a multiple bond to a group‐16 element (O, S, Se, Te) has been sought after [1–8] . Since boron is more electropositive than carbon, the resulting boron‐chalcogen double bonds are highly polarized compared to the carbonyl compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the synthetic importance of the carbonyl group, the synthesis of their main‐group analogs containing a multiple bond to a group‐16 element (O, S, Se, Te) has been sought after [1–8] . Since boron is more electropositive than carbon, the resulting boron‐chalcogen double bonds are highly polarized compared to the carbonyl compounds.…”
Section: Introductionmentioning
confidence: 99%
“…[18] The molecular structure of silanone 2 [19] reveals a planar geometry around the three-coordinated silicon atom (S si 8 = 358.398) and a short Si=O bond length [1.540 (3) ] which is longer than those of chromium-substituted silanone I (1.526 ) [10] and of dialkylsilanone V (1.518 ) [14] but is similar to those observed for other p-donor substituted silanones II-IV (1.533-1.543 ). [11][12][13] The N1-Si1 bond length [1.775 3] is almost identical to that of silylene 1 (1.771-1.781 ). Although the Si1-Rh bond [2.237(1) ] is slightly elongated compared to those of 1 (2.141-2.174 ), it is still shorter than classical Si(sp 2 )-Rh I bonds (2.30-2.35 ), [20] which suggests a remaining Rh-Si p-interaction.…”
mentioning
confidence: 98%
“…However, the synthesis of stable "base-free" silanones remains a difficult task. Indeed, although the recent studies demonstrated that bulky or/and strongly s-or/and p-donating substituents efficiently stabilize silanones I-V enough to be isolated in the crystalline form, [10][11][12][13][14] most of them remain unstable in solution at room temperature. To the best of our knowledge, only two silanones, such as the chromium-substituted cationic silanone I [10] and cyclic dialkylsilanone V, [14] are stable in solution at RT.…”
mentioning
confidence: 99%
“…[6] Even though some recent studies have demonstrated that bulky or/and strongly s-or/and p-donating substituents efficiently stabilize silanones, the synthesis of stable silanones I remains a great challenge and, to date, only a limited number of isolable silanones are available. [7][8][9][10][11][12] A drastic improvement in the stability was achieved by Driesss group, using donor (II) [13] or donor/acceptor (III) [14] systems. [15][16][17][18][19] Thanks to that, several stable and easy-tomanipulate silanone derivatives have been prepared.…”
mentioning
confidence: 99%
“…To date, only two stable transition-metal substituted silanones V have been described by Filippous group [7] and by us. [8] Particularly, the cyclic Rh Isubstituted silanone shows a unique reactivity associated with the two reactive centers (Si=O and Rh). However, in both cases, the desired intramolecular interaction to form a strained silanone-metal complex (type IV) was not observed.…”
mentioning
confidence: 99%